Turkey Jobs Diagnostic - Erdogan, Aysenur Acar; Del Carpio, Ximena V. (World Bank, Washington, DC, 2019)
The main challenge for achieving a country’s development goals is the creation of more, better and inclusive jobs, as economic growth needs to be accompanied by job growth if the poor are going to benefit to any significant extent. Turkey’s rapid economic growth since the early 2000s has been studied by the World Bank and others, highlighting the role of comprehensive reforms that promoted the country’s integration into the global economy, facilitated structural change, and catalyzed job creation. Therefore, the objective of this report is to present a comprehensive Jobs Diagnostic for Turkey with a view to promoting inclusive economic growth and poverty reduction. The report also aims to lay the evidence base to support policy dialogue in the country and provide input for the development of a national jobs strategy for the delivery of more, better, and inclusive jobs in Turkey. Understanding the factors that influence the creation of more, better and inclusive jobs essentially requires a multisectoral approach. Therefore, this jobs diagnostic aims to assess the relationships between supply- and demand-side factors.